Novel solution for leg motion with 5-link belt mechanism - Lovasz, Erwin; Pop, Florin; Pop, Cristian; Dolga, Valer (Zielona Góra: Uniwersytet Zielonogórski)
From the analysis of Theo Jansen walking mechanism and of the path curve that it describes the reduced capability for crossing over obstacles of the Jansen leg (1 DOF) is pointed out. By using a 5 link belt mechanism with 2 DOF can be adapted for generating similar Jansen mechanism path curve, where the step height of this path can be increased. For this purpose a mathematical model is conceived in order to analyse and determine the parameters for driving and control of the operation of the novel walking leg solution.
Keywords: walking leg; Jansen leg; 5-link belt mechanism; path generation; kinematic analysis